Enhanced superconductivity close to a non-magnetic quantum critical point in electron-doped strontium titanate - Yasuhide Tomioka (Nature Portfolio, 2019)
Among its interesting properties, SrTiO3 can show both superconductivity and ferroelectric quantum criticality at low temperatures. Tomioka et al. use La and oxygen-isotope doping to tune electron-doped SrTiO3 to the critical region and observe enhanced superconductivity, suggesting a link between them.